2012
DOI: 10.1111/j.1420-9101.2012.02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific genetics of speciation phenotypes: song and preference coevolution in Hawaiian crickets

Abstract: Understanding the genetic architecture of traits involved in premating isolation between recently diverged lineages can provide valuable insight regarding the mode and tempo of speciation. The repeated coevolution of male courtship song and female preference across the species radiation of Laupala crickets presents an unusual opportunity to compare the genetic basis of divergence across independent evolutionary histories. Previous studies of one pair of species revealed a polygenic basis (including a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Although there was a high degree of variation among the individuals (CV ranging from 21% to 58% with a similar distribution between the two species), PC analysis of the eight courtship song variables showed no significant differences between species ( F 1,20  = 0.75, P  = 0.41), populations ( F 2,20  = 0.19, P  = 0.89) or an effect of male age ( F 1,20  = 0.09, P  = 0.86). Pulse rate (the inverse of pulse period), which was suggested to be a driving factor in female preferences in Laupala cerasina and L. eukolea crickets [39], was more variable in G. firmus than G. pennsylvanicus (F- test, F 15,10  = 6.03, P < 0.05) but did not show differences in magnitude between the two species (Wilcoxon Rank Sum test U 11,16  = 123, P  > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Although there was a high degree of variation among the individuals (CV ranging from 21% to 58% with a similar distribution between the two species), PC analysis of the eight courtship song variables showed no significant differences between species ( F 1,20  = 0.75, P  = 0.41), populations ( F 2,20  = 0.19, P  = 0.89) or an effect of male age ( F 1,20  = 0.09, P  = 0.86). Pulse rate (the inverse of pulse period), which was suggested to be a driving factor in female preferences in Laupala cerasina and L. eukolea crickets [39], was more variable in G. firmus than G. pennsylvanicus (F- test, F 15,10  = 6.03, P < 0.05) but did not show differences in magnitude between the two species (Wilcoxon Rank Sum test U 11,16  = 123, P  > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The most conspicuous character differentiating the species is pulse rate of the male calling song, a sexually selected trait that is genetically regulated (Otte 1994; Shaw 2000a; Shaw 1996). Females show phonotactic preference for conspecific pulse rates (Shaw 2000b; Oh et al 2012), demonstrating that pulse rate may function as an interspecific mating barrier. Species of Laupala have also been shown to display daily behavioral rhythms whereby males sing and courting pairs mate at predictable times during daylight hours (Danley et al 2007; Fergus et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sex‐linked traits also tend to show higher evolutionary rates because they are more frequently expressed and thus more frequently exposed to selection (Qvarnström & Bailey, ). In line with earlier findings for Teleogryllus (Bentley & Hoy, ; Hoy, ) and Laupala crickets (Shaw, ; Shaw et al ., ; Oh et al ., ), we observed that the pulse rate and carrier frequency of reciprocal F1 hybrid cross lines resembled the maternal parent more than the paternal parent. The four F2 lines did not differ in their mean phenotype indicating that maternal effects are unlikely.…”
Section: Discussionmentioning
confidence: 97%
“…However, this method is highly sensitive to the presence of nonadditive genetic variation and even more to the sample size of the F2 hybrid or backcross generation (which should be over 100 following Lande, ) and is likely to provide biologically meaningless results given our data (Zeng et al ., ; Zeng, ). Nevertheless, based on our observations here, the studies of genetic control of song production in Australian Teleogryllus species (Bentley & Hoy, ; Hoy, ) and biometric and QTL mapping experiments in Hawaiian Laupala crickets (Shaw, ; Shaw et al ., ; Oh et al ., ), we infer that several unlinked loci (each potentially containing up to several genes) underlie the variation in song and preference traits.…”
Section: Discussionmentioning
confidence: 99%